Regulation of catecholamine release from the adrenal medulla is altered in deer mice (Peromyscus maniculatus) native to high altitudes - Scott, Angela L; Pranckevicius, Nicole A; Nurse, Colin A; Scott, Graham R (https://www.physiology.org/doi/full/10.1152/ajpregu.00005.2019, 2019)
High-altitude natives have evolved to overcome environmental hypoxia and provide a compelling system to understand physiological function during reductions in oxygen availability. The sympathoadrenal system plays a key role in responses to acute hypoxia, but prolonged activation of this system in chronic hypoxia may be maladaptive. Here, we examined how chronic hypoxia exposure alters adrenal catecholamine secretion and how adrenal function is altered further in high-altitude natives. Populations of deer mice (Peromyscus maniculatus) native to low and high altitudes were each born and raised in captivity at sea level, and adults from each population were exposed to normoxia or hypobaric hypoxia for 5 mo. Using carbon fiber amperometry on adrenal slices, catecholamine secretion evoked by low doses of nicotine (10 µM) or acute hypoxia (Po2 ∼15-20 mmHg) was reduced in lowlanders exposed to hypobaric hypoxia, which was attributable mainly to a decrease in quantal charge rather than event frequency. However, secretion evoked by high doses of nicotine (50 µM) was unaffected. Hypobaric hypoxia also reduced plasma epinephrine and protein expression of 3,4-dihydroxyphenylalanine (DOPA) decarboxylase in the adrenal medulla of lowlanders. In contrast, highlanders were unresponsive to hypobaric hypoxia, exhibiting typically low adrenal catecholamine secretion, plasma epinephrine, and DOPA decarboxylase. Highlanders also had consistently lower catecholamine secretion evoked by high nicotine, smaller adrenal medullae with fewer chromaffin cells, and a larger adrenal cortex compared with lowlanders across both acclimation environments. Our results suggest that plastic responses to chronic hypoxia along with evolved changes in adrenal function attenuate catecholamine release in deer mice at high altitude.